The role of financial accountability control in improving financial performance - Novandalina, Arini; Khajar, Ibnu; Ghoniyah, Nunung (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2024)
Purpose – This study aims to describe the effect of diversity of knowledge and financial capabilities on accountability for behavior control and improvement of financial performance.Design/methodology/approach – The population in this study were all branches of the Baitul Maal Wat Tamwil Sharia Savings and Loans Cooperative (KSPPS BMT) in Central Java. The sample used purposive sampling to obtain 146 respondents. Data were analyzed using the Structural Equation Modeling (SEM) analysis technique with the application of Analysis Moment of Structural (AMOS 24).Findings – The results of the study explain the increase in financial performance based on Behavioral Accounting Theory and Human Resource Management Theory. The behavior control accountability model shows that perceived interest and intention in self-confidence to control accountability behavior as indicated by behavioral intention, perceived behavioral control, process and financial accountability can affect financial performanceResearch limitations/implications – Where the factors of diversity of knowledge and financial capability in shaping accountability for behavior control and impact on financial performance will offer a deeper understanding of the supporting factors for accountability for behavior control and also have an impact on efforts to improve financial performance.Practical implications – A better understanding of the factors influencing improvement efforts should assist accountants in information processing, quality of judgments, accounting problems that arise with accounting users and preparers, and the use of information in accounting decision making.Originality/value – Using and explaining about improving financial performance based on Behavioral Accounting Theory and Human Resource Management Theory. The behavior control accountability model shows that perceived interest and intention in self-confidence to control accountability behavior as indicated by behavioral intention, perceived behavioral control, process and financial accountability can affect financial performance